A formação na licenciatura em Educação do Campo para atuar com a disciplina de Física na educação básica - FORMIGOSA, Marcos Marques (Universidade Federal da Fronteira Sul, 2020)
The Graduation‟s courses in Rural Education have, among its differentials, the training by knowledge area, among them, the Nature Sciences which, in some Pedagogical Projects of Courses (PPC), enables the egresses to work in High School with the scholars disciplines of Biology, Chemistry and Physics. In this sense, the objective of this research is to investigate how has been occurring the training of the teacher who will work in the discipline of Physics, at Basic Education, from a Degree course in Rural Education. The information production technique was documentary research in databases of Census of Higher Education and Basic Education, from 2018 and 2019, respectively, besides a PPC of a Rural Education course which is functioning in the interior of the State of Pará. These data were analyzed in a qualitative perspective and show that there is a high percentage of teachers who work in this discipline without proper training due the low quantity of teachers of Physics who graduate in the country. This percentage becomes more accentuated when we look at active teachers in the rural schools. In addition, it shows that the workload of the curricular activities in the Rural Education course destined to the Physics discipline is too low corresponding only to 7,2% of the total, besides the contents which are in these activities menus be predominant of the classic Physics suggesting that there is no addressing which connect them with the ways of life of the country man.